2007
DOI: 10.1038/sj.embor.7400979
|View full text |Cite|
|
Sign up to set email alerts
|

Necessary and sufficient factors for the import of transfer RNA into the kinetoplast mitochondrion

Abstract: The mechanism of active transport of transfer RNA (tRNA) across membranes is largely unknown. Factors mediating the import of tRNA into the kinetoplast mitochondrion of the protozoon Leishmania tropica are organized into a multiprotein RNA import complex (RIC) at the inner membrane. Here, we present the complete characterization of the identities and functions of the subunits of this complex. The complex contains three mitochondrion-and eight nuclear-encoded subunits; six of the latter are necessary and suffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 19 publications
0
41
1
Order By: Relevance
“…To date, the R NA i mport c omplex (RIC) of Leishmania tropica is by far the system with the most proteins proposed to import tRNAs into mitochondria 8890 . Mass spectrometry analyses of the multi-protein ~580 kDa L. tropica RIC revealed a total of 122 nuclear-encoded ORFs 88 .…”
Section: Trna Import Into Mitochondriamentioning
confidence: 99%
“…To date, the R NA i mport c omplex (RIC) of Leishmania tropica is by far the system with the most proteins proposed to import tRNAs into mitochondria 8890 . Mass spectrometry analyses of the multi-protein ~580 kDa L. tropica RIC revealed a total of 122 nuclear-encoded ORFs 88 .…”
Section: Trna Import Into Mitochondriamentioning
confidence: 99%
“…To date, one of the most studied import systems is that of Leishmania , where a putative R NA i mport c omplex (RIC) in L. tropica has been identified (Mukherjee et al, 2007). This complex contains a number of proteins known to serve alternative functions in respiration, introducing the concept of a `moonlighting' function for these proteins.…”
Section: Factors and Determinants Of Trna Importmentioning
confidence: 99%
“…This complex contains a number of proteins known to serve alternative functions in respiration, introducing the concept of a `moonlighting' function for these proteins. The core import complex contains six essential factors required for both in vivo and in vitro import: α subunit of the F 1 -ATP synthase, subunit 6b and the Rieske protein of the respiratory complex III, two proteins with no similarities to any other proteins in the database and lastly subunit 6 of the respiratory complex IV (Mukherjee et al, 2007). As part of our studies we have also explored the possibility of the RIC as a conserved feature of import in T. brucei .…”
Section: Factors and Determinants Of Trna Importmentioning
confidence: 99%
“…Yet, in the L. tropica strain used by the Adhya group, the antisense strategy seems to work extremely efficiently. Moreover, reconstitution of the RIC complex-consisting of six different proteinsinto liposomes was done starting from denatured proteins that were eluted from sodium dodecyl sulphate (SDS) gels and refolded (Mukherjee et al 2007). While this might not be impossible, we are not aware of any precedent where such an approach has worked.…”
Section: Lysmentioning
confidence: 99%
“…The inner membrane tRNA import machinery of L. tropica appears to consist of an unconventional protein complex of approximately 580 kDa, termed tRNA import complex (RIC), that was initially characterized by affinity chromatography using an RNA oligonucleotide consisting of an in vitro-defined tRNA-import signal (Goswami et al 2006). Mass spectrometry analysis revealed that RIC consists of 11 major subunits, eight of which are nucleus-encoded and three that are mitochondria-encoded (Mukherjee et al 2007). Six of the former are essential for tRNA import and four are identical to subunits of different respiratory Review.…”
Section: Lysmentioning
confidence: 99%